Product design: An optimization-based approach for targeting of particulate composite microstructure. (2nd September 2020) - Mushtaq, Faheem; Zhang, Xiang; Fung, Ka Yip; Ng, Ka Ming
Abstract: The microstructure of a particulate composite with given ingredients has enormous influence on its physicochemical properties. An optimization-based approach is presented for determining the target of two-component particulate composite microstructure. The dominant physicochemical phenomena are captured by the relevant gradient-based transport equations. Particles of different size, shape, and orientation are placed in the composite to maximize a desired physicochemical property. The formulated problem is readily solved via mixed-integer non-linear programming. A case study is performed on the design of a die attach adhesive the objective of which is to obtain the maximum effective thermal conductivity at different loadings of the nano filler particles.